"What is the problem represented to be?" Two decades of research on Roma and education in Europe. (June 2018) - Lauritzen, Solvor M.; Nodeland, Tuva S.
Abstract: This review article offers an analysis of research on Roma and education. A total of 151 peer-reviewed research articles were sampled through systematic searches in four databases, covering the period 1997–2016. Inspired by critical approaches in policy analysis, we draw on the concept of problem representations to identify dominant discourses in the research material. The analysis identifies nine problem representations; absence from school, academic achievement, socioeconomic issues, cultural differences, invisibility, teachers' competencies, hostility, segregation and misguided policy and action. The content of these problem representations suggests that Roma is often framed as either victims or problems in educational research, and that cultural differences are much more dominant as a problem representation in the field than structural aspects such as socioeconomic issues. This critical review can contribute to raise awareness regarding how we frame research questions in the field of Roma and education. Highlights: A systematic search identifies 151 peer-reviewed articles on Roma and education. Abstracts are analyzed inspired by policy-as-discourse -theory. Nine problem representations are identified in research on Roma and education. Cultural differences are more frequently addressed than socioeconomic issues. Roma is primarily perceived as either problem or victim, and rarely as a resource.